Analysis of the vocabulary of the «nursery language» in multilevel idioms (based on the material of the Rutul language) - M.O. Ibragimova (Язык и текст)
Based on a comparative analysis of the factual material of the Rutul dialects of the Nakh-Dagestan language family, the article aims to identify the features of the "nanny language" used by adults when communicating with children and which is the object of ontolinguistics, a branch of linguistics that studies the early stages of speech development. The first primitive (babbling, onomatopoeic, and interjective words) and lexemes of a more advanced stage of children's language development are given as illustrative material. An attempt has been made to identify quantitative and qualitative differences in the vocabulary of the children's language of idioms of different levels: the Muhad dialect, which underlies the literary language being formed, the Ihrek, Mykhrek dialects and Borch subdialect. It is revealed that the richness of the vocabulary of children's vocabulary in dialects and subdialects is due to the presence of innovations in the written standardized language.